Circumcision in a combined factor V and factor VIII deficiency using desmopressin (DDAVP) - Devecioğlu, Ömer; Eryılmaz, Ertuğrul; Çelik, Dicle; Ünüvar, Ayşegül; Karakaş, Zeynep; Anak, Şema; Ağaoğlu, Leyla (The Turkish Journal of Pediatrics, 2002)
Combined factor V and VIII deficiency is a rare inherited autosomal recessive single gene disorder commonly seen in the Middle East. Although the factor levels are between 5-30%, several authors have reported that these patients are more prone to bleeding compared to those having an isolated factor deficiency with the same levels. We report an eight-year-old boy with factor V and VIII deficiency who underwent a successful circumcision using desmopressin (DDAVP).